Analysis of Pandemic Bussnines Strategy Development at PT Milala Wisata Tour and Travel - Panjaitan, Andreas; Stefen Sembiring, Andes; Christine Sembiring , Anita; Budiman, Irwan (Journal Knowledge Industrial Engineering (JKIE), 2021)
The research is the qualitative and quantitative results using SWOT, STP, Marketing mix 7P, and cashflow for 3 years method analysis. This research aims to develop the business of PT Milala Wisata Tour & Travel during Covid-19 pandemic by using a typical culinary side business so that the main business can survive. SWOT analysis is a way to systematically identify various factors in order to formulate company strategy. The data collection technique carried out by the researcher is by direct observation conducted at the company and conducting interviews with the owner of PT. Milala Wisata Tour & Travel. Also by adding from reading books and also other sources related to the research title. The 7P Marketing mix includes price, product, process, people, physical evidance, promotion, place. To find out the strengths, weaknesses, and feasibility of typical culinary side businesses, an analysis is first carried out to find out how the target market is The data obtained from the collection and then analyzed using the Internal Rate of Return & Cashflow for 3 years to see the feasibility level of typical culinary side businesses are suitable and able to support the main business of the The results of research from Cashflow for 3 years show that a typical culinary side business deserves to be realized as a support for main business during the Covid-19 pandemic. Typical culinary side businesses have strengths and are in line with the travel business so they can take advantage of existing opportunities.